ABO blood groups and hepatitis B virus infection: a systematic review and meta-analysis - Jing, Wenzhan; Zhao, Siyu; Liu, Jue; Liu, Min (BMJ open, 2020)
ObjectiveHepatitis B virus (HBV) infection is a major public health problem worldwide. Several studies have reported that ABO blood groups may be associated with HBV infection. However, its association is still controversial. We performed a meta-analysis to investigate whether ABO blood groups were associated with HBV infection.DesignSystematic review and meta-analysis.Data sourcesRelevant studies available before 1 December 2019 were identified by searching PubMed, EMBASE, Web of Science, ScienceDirect and the Cochrane Library.Eligibility criteriaAll cross-sectional or cohort studies from which the data of ABO blood group distribution and HBV infection could be extracted.Data extraction and synthesisStudies were identified and extracted by two reviewers independently. Risk ratios (RRs) and 95% CIs were pooled by random-effect models to quantify this association.ResultsThirty-eight eligible articles including 241 868 HBV-infected subjects and 6 487 481 uninfected subjects were included. Overall, the risk of HBV infection had decreased by 8% in subjects with blood group B when compared with non-B blood group (RR=0.92, 95% CI 0.86 to 0.98). In the subgroup analyses, the inverse relationship between blood group B and HBV infection remained stable in higher endemic areas (HBV prevalence ≥5%), Asian people, larger sample size studies (≥2000), general population and blood donors, lower middle income group and studies published before the year 2010. Additionally, subjects with blood group O had a 12% increased risk of HBV infection (RR=1.12, 95% CI 1.01 to 1.24) in higher endemic areas. In the sensitivity analysis, the pooled risk estimates of blood group B and HBV infection were still stable.ConclusionsOur data suggested that the blood group B was associated with a lower risk of HBV infection. More research is needed to clarify the precise role of the ABO blood group in HBV infection to address the global question of HBV infection.